Self-Control as a Core Component of Professional Competence of IT Students - Milana F. Bakunovich; Natalia L. Stankevich (National Research Mordova State University, 2018)
Introduction. With jobs becoming more stressful, professional competences in solving tactical and strategic tasks grow in importance. The systematic self-control in stressful environment helps to find a rational approach, provides for work's accuracy and productivity. It is important to study IT-students self-control experimentally as far as there is a discrepancy between employers' demands and young employees' skills. The article reveals the issue of self-control and highlights its importance. The authors present their experimental findings on IT-specialists' self-control in stressful working conditions. Materials and Methods. The experiment exploits methodological triangulation and involves both qualitative (interview, observation) and quantitative (tests) research. Content-analysis and statistical methods were applied. Results. The emotional control deteriorates under conditions of monotony and time-pressure. The attention of IT-students is unsustainable. Their actions become slower and less precise. The lack of self-control is observed. Discussion and Conclusion. The self-control is essential for professional competence of IT students. The latter lacks self-control under stress. The article considers perspective ways of the self-control development. The findings have practical importance for psychologists and educators. They can be applied in psychological support programs for high school and university students as well as for self-control training. Further studies should focus on IT-students' self-control formation and enhancement.